2022
DOI: 10.1007/s00018-022-04541-6
|View full text |Cite
|
Sign up to set email alerts
|

The ERK5/NF-κB signaling pathway targets endometrial cancer proliferation and survival

Abstract: Endometrial cancer (EC) is the most common type of gynecologic cancer in women of developed countries. Despite surgery combined with chemo-/radiotherapy regimens, overall survival of patients with high-risk EC tumors is poor, indicating a need for novel therapies. The MEK5-ERK5 pathway is activated in response to growth factors and to different stressors, including oxidative stress and cytokines. Previous evidence supports a role for the MEK5-ERK5 pathway in the pathology of several cancers. We investigated th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…[ 22 ] EGFR tyrosine kinase inhibitor is a small molecule EGFR inhibitor that can inhibit tyrosine kinase activation, block the EGFR signaling pathway, inhibit the proliferation and metastasis of tumor cells, and promote apoptosis through competitive endogenous ligand binding to EFGR. [ 23 ] Therefore, lncRNA may regulate the occurrence and development of tumors by regulating the expression of target genes by participating in the functional and signaling pathways listed above.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] EGFR tyrosine kinase inhibitor is a small molecule EGFR inhibitor that can inhibit tyrosine kinase activation, block the EGFR signaling pathway, inhibit the proliferation and metastasis of tumor cells, and promote apoptosis through competitive endogenous ligand binding to EFGR. [ 23 ] Therefore, lncRNA may regulate the occurrence and development of tumors by regulating the expression of target genes by participating in the functional and signaling pathways listed above.…”
Section: Discussionmentioning
confidence: 99%
“…A range of studies involving genetic perturbation of ERK5 with siRNA/shRNA-mediated gene silencing or deletion of the MAPK7 gene (encoding ERK5) suggests that ERK5 signaling has a role in driving several distinct cellular phenotypes. Gene silencing of ERK5 has been shown to be antiproliferative in vitro or in vivo in a number of cancer cell types, including endometrial cancer, nonsmall cell lung cancer (NSCLC), small cell lung cancer (SCLC), melanoma, triple-negative breast cancer, and cholangiocarcinoma . In SCLC, a reduction in tumor cell proliferation upon ERK5 shRNA knockdown was not rescued by kinase-dead ERK5, in contrast to wild-type ERK5, suggesting that ERK5 kinase activity is important in mediating proliferation in this tumor type .…”
Section: Genetic Perturbation Of Erk5mentioning
confidence: 99%
“…JWG-071 exhibits greatly (>10-fold) improved selectivity for ERK5 over BRD4 in comparison to XMD8-92 but retains much of XMD8-92’s potency toward other kinases including LRRK2, DCAMKL1, and PLK4. , The improved selectivity over BRD4 has been attributed to steric clash of the sec -butyl group with the αC-helix of BRD4. Interestingly, JWG-071 has demonstrated tumor-suppressive activity in endometrial cancer xenografts with intraperitoneal administration …”
Section: Evolution Of Inhibitors Of the Erk5 Kinase Domainmentioning
confidence: 99%
“…Therefore, MEK5 knockout cells lack ERK5 kinase activity. We recently reported that MEK5-KO Ishikawa cells, while lacking ERK5 activity, show normal activation of other MAP kinases (ERK1/2, p38s or JNKs), or components of the PI3K pathway (Akt, mTORC1 or p70S6K) in response to mitogens, stressors or insulin 20 . On the other hand, ERK5-KO cells lack both kinase activity-dependent and -independent functions.…”
Section: Erk5 Kinase Activity Modulates Sensitivity Of Cancer Cell To...mentioning
confidence: 99%